Finding the optimal way to build an information security system based on Markov chains - A. M. Konakov; I. I. Livshits (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The study examined the main aspects of building an information security system from the point of view of optimizing the resources spent and funds to ensure information security. Method. In this subject area, the possibilities of structural-parametric models and Markov chains for identifying the optimal line for constructing a multi-level information security system are considered. Practice shows that the construction and implementation of a multi-level information security system reduces the possibility for an attacker of compromise and unauthorized access to protected information. Result. An analysis of the functionality of the constructed models was carried out as a means of finding the optimal way to build an information security system. An assessment of information security risks was carried out at the most vulnerable points in the information security processes. An approach to building a multi-level information security system using the functionality of structural-parametric models and Markov chains has been developed and proposed. A pattern has been formulated that makes it possible to determine the correctness of the constructed information security system based on the analysis and assessment of information security risks at the most vulnerable points of a multi-level information security system, in the process of transition from one state to another. Conclusion. Ensuring information security using mathematical modeling methods is a relevant and valuable tool based on the dynamism of threats and their uncertainty at different periods of time. The development, testing and implementation of new approaches based on modeling allows us to predict and prevent the most likely actions and steps of an attacker, thereby reducing the level of risk and possible damage to protected information resources and systems.